The The validity of Kohlrausch law for the photocurrent transient and the role of N2/Ar flow ratio in photoconductivity of sputtered CoZnO - Soylu, M.; Coskun, B.; Al-Sehemi, Abdullah G.; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2017)
Co:ZnO (CZnO) ferromagnetic semiconductor layers are coated on the surface of glass and Si substrates by Magnetron Sputter Deposition Method (MSDM) with variable N-2/Ar gas flow ratio. N-2/Ar flow ratio varies from 5 sccm to 20 sccm, keeping the Ar gas flow constant (at 30 sccm). Sample's surface topography-composition, structure and optic properties are characterized by scanning electron microscope (SEM), X-ray diffraction (XRD) and ultraviolet visible (UV/Vis) spectrophotometry. CZnO/p-Si structure exhibits both rectifying and photovoltaic behavior. Kohlrausch decay function is used to model the photocurrent transient curve and the associated relaxation process. The values of the photo charge density (rho(ph)) and the relaxation time constant (tau(0)) are found to be 1.02 x 10(11) Coul/cm(-2) and 1.1 x 10(4) s, respectively. These findings suggest that CZnO/p-Si structure can be used in photodetector applications. The photoconductivity of the device can be tuned with the N-2/Ar flow ratio since the property of CZnO thin films deposited from 3% Co doped ZnO target is dependent on the N-2 and Ar atmosphere. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Kohlrausch; Sputtering; ZnO; I/C-V characteristics; Phototransient measurements